Novel bone morphogenetic protein signaling through Smad2 and Smad3 to regulate cancer progression and development. Issue 3 (5th December 2013) - Holtzhausen, Alisha; Golzio, Christelle; How, Tam; Lee, Yong‐Hun; Schiemann, William P.; Katsanis, Nicholas; Blobe, Gerard C.
Abstract : The bone morphogenetic protein (BMP) signaling pathways have important roles in embryonic development and cellular homeostasis, with aberrant BMP signaling resulting in a broad spectrum of human disease. We report that BMPs unexpectedly signal through the canonical transforming growth factor β (TGF‐β)‐responsive Smad2 and Smad3. BMP‐induced Smad2/3 signaling occurs preferentially in embryonic cells and transformed cells. BMPs signal to Smad2/3 by stimulating complex formation between the BMP‐binding TGF‐β superfamily receptors, activin receptor‐like kinase (ALK)3/6, and the Smad2/3 phosphorylating receptors ALK5/7. BMP signaling through Smad2 mediates, in part, dorsoventral axis patterning in zebrafish embryos, whereas BMP signaling through Smad3 facilitates cancer cell invasion. Consistent with increased BMP‐mediated Smad2/3 signaling during cancer progression, Smad1/5 and Smad 2/3 signaling converge in human cancer specimens. Thus, the signaling mechanisms used by BMPs and TGF‐β superfamily receptors are broader than previously appreciated.—Holtzhausen, A., Golzio, C., How, T., Lee, Y.‐H., Schiemann, W. P., Katsanis, N., Blobe, G. C. Novel bone morphogenetic protein signaling through Smad2 and Smad3 to regulate cancer progression and development. FASEB J. 28, 1248–1267 (2014). www.fasebj.org